Pax-Six-Eya-Dach network during amphioxus development: conservation in vitro but context specificity in vivo - Kozmik, Zbyněk; Holland, Nicholas D; Jelínková, Jana; Oliveri, Diana; Schubert, Michael; Marková, Kristýna; Holland, Linda Z; Pestarino, Mario; Beneš, Vladimír; Candiani, Simona (Developmental biology, 2007)
The Drosophila retinal determination gene network occurs in animals generally as a Pax-Six-Eyes absent-Dachshund network (PSEDN). For amphioxus, we describe the complete network of nine PSEDN genes, four of which-AmphiSix1/2, AmphiSix4/5, AmphSix3/6, and AmphiEya-are characterized here for the first time. For amphioxus, in vitro interactions among the genes and proteins of the network resemble those of other animals, except for the absence of Dach-Eya binding. Amphioxus PSEDN genes are expressed in highly stage- and tissue-specific patterns (sometimes conspicuously correlated with the local intensity of cell proliferation) in the gastrular organizer, notochord, somites, anterior central nervous system, peripheral nervous system, pharyngeal endoderm, and the likely homolog of the vertebrate adenohypophysis. In this last tissue, the anterior region expresses all three amphioxus Six genes and is a zone of active cell proliferation, while the posterior region expresses only AmphiPax6 and is non-proliferative. In summary, the topologies of animal PSEDNs, although considerably more variable than originally proposed, are conserved enough to be recognizable among species and among developing tissues; this conservation may reflect indispensable involvement of PSEDNs during the critically important early phases of embryology (e.g. in the control of mitosis, apoptosis, and cell/tissue motility).
Keywords: financování organizované; Animals; Chordata; Kidney; epidermis; Epidermis; Active Transport, Cell Nucleus; Epidermal Cells; epidermální buňky; adenohypofýza; homeodoménové proteiny; messenger RNA; aktivní transport - buněčné jádro; proteiny nervové tkáně; RNA, Messenger; Financing, Organized; Phylogeny; Central Nervous System; Neurons, Afferent; Pituitary Gland, Anterior; Nerve Tissue Proteins; neurony aferentní; Homeodomain Proteins; exprese genu; zvířata; centrální nervový systém; fylogeneze; ledviny; Gene Expression